PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT AMTEK ENGINEERING BATAM - Silvia Janerista Ompusunggu (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
This study aims to analyze how much the impact of organizational culture and work motivation on employees at PT Amtek Engineering Batam. This study uses a quantitative approach by taking several samples from PT Amtek Engineering Batam employees with a total of 186 respondents, using data collection techniques in the form of questionnaires to measure directly how much influence, with primary data and find human resource information for organizational culture. Creating organizational culture and work motivation of PT Amtek Engineering Batam employees. In this study, data collection techniques used simple random sampling by taking samples from a population using random sampling, that is, without regard to hierarchy (level). Because all members of the population are considered to be the same (homogeneous), researchers use the Slovin formula with an error rate (e) of 5%. As a tool to determine the number of samples, 59 male respondents, 127 female respondents, the t-test is known, the f-test is 1,972 for the t-test and 3.0 for the f-test. So this study can be concluded that organizational culture (X1) and work motivation (X2), affect the performance of employees (Y). While the third hypothesis (H_3) is accepted. This study uses the SPSS version 25 statistical application.